PENINGKATAN KEMAMPUAN BAHASA LISAN ANAK KELOMPOK B PAUD RERAWETE MELALUI METODE PEMBELAJARAN MENGGUNAKAN MEDIA GAMBAR BERSERI - Nyamin, Elisabeth Yuniarti; Ngura, Elisabeth Tantiana; Dua Dhiu, Konstantinus; Laksana, Dek Ngurah Laba (Jurnal Citra Pendidikan, 2025)
Abstract Early childhood, because it serves as the foundation for effective communication and learning in the future. This research aims to B TK Rerawete through a learning method that uses a series of picture media. This method was chosen because it provides engaging visual stimulation and helps children understand the storyline logically. This research uses the Classroom Action Research approach, which is conducted in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The subjects of the study are 12 children from Group B of Paud Rerawete. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively and quantitatively. The use of series of pictures as media to improve language skills in the speaking aspect for early childhood children at Paud Rerawete employs data collection methods through observation, interviews, and documentation. The research results show that the use of sequential picture media can significantly improve children's oral language skills. The improvement is evident in aspects of speaking fluency, the courage to express opinions, and the ability to construct a coherent story. In cycle I, the percentage of children's language proficiency reached 33.3%, and increased to 83.3% in cycle II. Thus, the learning method using a series of picture media has proven effective in improving the oral language skills of early childhood children.